Theoretical study of the molecular aspect of the suspected novichok agent A234 of the Skripal poisoning - Hanusha Bhakhoa (Royal Society Open Science, 2019)
Novichoks are the suspected nerve agents in the March 2018 Skripal poisoning. In this context, the novichok agent A234 (chemical structure proposed by Mirzayanov) was studied using computational methods to shed light on its molecular, electronic, spectroscopic, thermodynamic and toxicity parameters as well as on potential thermal and hydrolysis degradation pathways. The poisoning action and antidote of A234 were also investigated. Some of these parameters were compared to three common G- and V-series nerve agents, namely GB, VR and VX. The research findings should be useful towards the detection, development of antidotes and destruction of A234.